Penyuluhan E-Commerce dan Produk Chili Oil sebagai Solusi UMKM Dusun Sukamulya - Widyowati, Weny; Muhammad, Muzzi; Zakiya, Aliya; Hartanto, Harry Rahmat; Hapsari, Cornelia Indra; Salsabila, Pradita Dina; Ratnapuri, Kurnia; Surya, Muhamad Satria Hady; Zahran, Nurul Zalfa Zainum; Armanto, Rajendra Gavin; Tuffahati, Nadhira; Ariaputra, Adji Gilang Riano; Dewa, Wijaya Riangsa; Asril, Muhammad Fakhri (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Community empowerment is an effort to improve welfare by developing human resource potential. Dusun Sukamulya, Genteng Village, Sumedang Regency, has diverse agricultural products that have not been optimally utilized to increase their economic value. To overcome this problem, students and lecturers of the Communication Science Study Program, Universitas Padjadjaran, class of 2021, held an MSME-based empowerment program with a focus on processing agricultural commodities, especially chilies, into chili oil. This activity includes counseling and demonstrations of making ready-to-sell products and an introduction to digital marketing through e-commerce. The approach used is persuasive and educational communication to encourage active community participation. The activity results showed an increase in residents' understanding of local commodity-based business opportunities and a growing interest in starting independent businesses. The community's enthusiasm as beneficiaries supported the success of this program. Thus, this empowerment program contributes to creating new economic opportunities for residents of Dusun Sukamulya by optimising local agricultural potential